2003
DOI: 10.1093/ajcn/78.4.734
|View full text |Cite
|
Sign up to set email alerts
|

An increase in dietary protein improves the blood glucose response in persons with type 2 diabetes

Abstract: A high-protein diet lowers blood glucose postprandially in persons with type 2 diabetes and improves overall glucose control. However, longer-term studies are necessary to determine the total magnitude of response, possible adverse effects, and the long-term acceptability of the diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
268
3
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(298 citation statements)
references
References 38 publications
10
268
3
8
Order By: Relevance
“…We found no significant difference in glycaemic control between subjects on the two diets. In contrast, a small study of 12 obese subjects with Type 2 diabetes showed a small, but significant improvement in HbA 1 c over 5 weeks on a weight-maintaining highprotein diet containing a protein : carbohydrate : fat ratio of 30:40:30, compared to an isocaloric low-protein diet (15:55:30) [10]. Since LBM is associated with glycaemic control [26], it is possible that the loss of LBM in our subjects may have masked any small effect of diet on glucose control.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found no significant difference in glycaemic control between subjects on the two diets. In contrast, a small study of 12 obese subjects with Type 2 diabetes showed a small, but significant improvement in HbA 1 c over 5 weeks on a weight-maintaining highprotein diet containing a protein : carbohydrate : fat ratio of 30:40:30, compared to an isocaloric low-protein diet (15:55:30) [10]. Since LBM is associated with glycaemic control [26], it is possible that the loss of LBM in our subjects may have masked any small effect of diet on glucose control.…”
Section: Discussionmentioning
confidence: 86%
“…Several short-term, randomised, controlled studies (≤6 months duration) have shown that the replacement of some dietary carbohydrate with protein in low-fat diets (≤30%) enhances weight loss [7], is associated with favourable changes in body composition [7,8,9] and exerts beneficial effects on CVD risk factors, including insulin sensitivity [8], glycaemic control [10,11] and lipid profile [8,9,12]. While these diets may offer modest short-term metabolic advantages, to date, there are no long-term clinical trials of their long-term efficacy, safety and acceptability compared to conventional low-fat, high-carbohydrate diets in persons with Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies showed better glycemic control and insulin sensitivity in patients taking lower levels of carbohydrate23, 24, 25, whereas some others showed no difference26, 27. Conflicting results were also reported by various studies regarding the clinical outcomes in patients having higher or usual protein intake28, 29, 30, 31. Eating plans and nutrition therapy goals should be set collaboratively with individual needs including the patients’ metabolic targets, personal and cultural preferences, literacy and economic capability, as well as their ability and willingness to change16.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence indicates that insulin sensitivity, which can be affected by diet 4 , is an important determinant of ovulatory function and fertility 5,6 . The amount and sources of protein in diet have been found to influence insulin sensitivity [7][8][9][10] , yet high-protein, lowcalorie diets have been found not to influence reproductive parameters beyond their effects on weight loss in women with polycystic ovary syndrome (PCOS) 11,12 . However, it is not currently known whether the amount or source of dietary protein affects ovulatory function or fertility among healthy women not in weight loss diets.…”
Section: Introductionmentioning
confidence: 99%